Ultrahigh-temperature-resistant carbon fiber composite filter material and production system thereof

Through computer simulation, optimize material proportions, combined with pretreatment, modification treatment and composite technology, the performance fluctuations caused by the difference in material proportions during preparation of carbon fiber composite filter materials are solved, and the consistency of material performance and high temperature resistance are achieved. .

CN119488758APending Publication Date: 2025-02-21JIANGSU FMS ENVIROMENTAL&ENERGY SAVING NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411667696.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In the prior art, performance fluctuations caused by differences in material proportions during preparation of carbon fiber composite filter materials lead to the risk of inapplicability of materials and unnecessary waste.

Method used

Through computer simulation technology, optimize the material combination ratio, select high-quality carbon fibers and resins, and perform pretreatment and modification treatment, combine impregnation and curing technology to design composite structures, and finally surface polishing and coating with high-temperature resistant coatings.

Benefits of technology

It significantly reduces performance fluctuations caused by material proportion differences, ensures the performance consistency and repeatability of composite materials, improves high temperature resistance and durability, and reduces the risks and waste caused by material inapplicability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488758A_ABST
    Figure CN119488758A_ABST
Patent Text Reader

Abstract

The invention provides an ultrahigh-temperature-resistant carbon fiber composite filter material and a production system thereof, and relates to the field of composite filter material production. An ultrahigh-temperature-resistant carbon fiber composite filter material production system comprises the following steps: S1, using amount optimization through a computer simulation technology so as to predict an optimal material combination ratio, S2, selecting high-quality carbon fibers and resin as a composite resin material according to a simulation result, S3, pretreating the carbon fibers, modifying the resin, and S4, preparing the ultrahigh-temperature-resistant carbon fiber composite filter material. The method comprises the following steps: S1, preparing a polyimide resin matrix, S2, preparing a polyimide resin matrix, S4, designing a composite structure of the filter material, S5, combining carbon fibers with the polyimide resin matrix through dipping treatment to form a composite material with high strength and light weight, S6, placing the composite material in a mold for curing and cooling, and S7, carrying out surface polishing and grinding on the molded composite filter material, and coating a high-temperature-resistant coating. And S8, obtaining the formed ultrahigh-temperature-resistant carbon fiber composite filter material. The material performance is verified by simulating the ratio of the resin to the carbon fibers, and performance fluctuation caused by material proportion difference is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite filter material production, in particular to an ultra-high temperature resistant carbon fiber composite filter material and a production system thereof. Background Art

[0002] Ultra-high temperature resistant carbon fiber composite filter material is a special advanced material, mainly composed of carbon fiber and resin, designed to withstand extreme temperatures and harsh environmental conditions. This type of material is known for its excellent mechanical properties and thermal stability and is widely used in fields that require high temperature filtration and separation functions.

[0003] In certain industrial applications and extreme environments, such as rocket engines, melting furnaces and other high-temperature processes, materials may be exposed to temperatures exceeding 300°C, or even extreme conditions as high as 2000°C. In this case, traditional materials often cannot meet the requirements of high temperature resistance, wear resistance and chemical stability. In the prior art, the conventional means of making carbon fiber composite filter materials is to select high-performance carbon fiber as a reinforcing material and perform surface treatment on it to enhance the bonding strength with the resin; then, the resin (such as epoxy resin or thermoplastic resin) is mixed with the carbon fiber in a certain proportion, and the resin is evenly covered on the carbon fiber by impregnation or spraying; then, hot pressing or curing treatment is performed to ensure that the resin forms a stable composite structure during the curing process; finally, after cutting and post-processing, the prepared carbon fiber composite filter material is processed into the required shape and size to meet specific application requirements, but there is still room for improvement in high temperature resistance. The performance fluctuations caused by the difference in material proportions during preparation are likely to cause the risk of material inapplicability and cause unnecessary waste. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides an ultra-high temperature resistant carbon fiber composite filter material and a production system thereof, which solves the problem of performance fluctuations caused by differences in material proportions.

[0005] To achieve the above objectives, the present invention is implemented by the following technical solutions: a production system of ultra-high temperature resistant carbon fiber composite filter material, comprising the following steps: S1, optimizing the dosage by computer simulation technology to predict the best material combination ratio;

[0006] S2, selecting high-quality carbon fiber and resin as composite resin materials according to the simulation results;

[0007] S3, pre-treating the carbon fiber and modifying the resin;

[0008] S4. Design of filter material composite structure;

[0009] S5, combining carbon fibers with a polyimide resin matrix through an impregnation process to form a high-strength, lightweight composite material;

[0010] S6, placing the composite material inside the mold for solidification and cooling;

[0011] S7, polishing and grinding the surface of the formed composite filter material, and applying a high temperature resistant coating;

[0012] S8, obtaining a molded ultra-high temperature resistant carbon fiber composite filter material.

[0013] Preferably, the specific steps of computer simulation ratio are as follows: S11, first, the physical and chemical property data of different types of fibers and resins are collected by computer, including strength, modulus, weight, temperature resistance, corrosion resistance, etc., which can be derived from experimental tests and literature data, the selected carbon fibers include: PAN-based carbon fibers and asphalt-based carbon fibers, and the selected resins include: polyimide, epoxy resin and phenolic resin;

[0014] S12. Use finite element analysis (FEA) software to establish a performance model of carbon fiber composite materials and simulate the performance changes of composite materials under different conditions;

[0015] S13. Apply the particle swarm optimization algorithm to iteratively analyze the model to find the optimal fiber-resin ratio, predict the material's strength, stiffness, weight ratio and other performance indicators under specific load conditions, and evaluate the composite material's strength, stiffness and fatigue life under different conditions through the simulated stress and strain distribution diagrams;

[0016] S14. Experimentally verify the optimal ratio scheme generated by computer simulation to ensure that the simulation results are consistent with the actual performance.

[0017] Preferably, the experimental test in S11 evaluates the physical and chemical properties of the fiber and the resin by means of tensile test, compression test, thermogravimetric analysis, differential scanning calorimeter, etc., and the obtained data are collected in a computer database.

[0018] Preferably, the computer simulation ratio results are as follows:

[0019] PAN-based carbon fiber and polyimide resin, the ratio is 30:70;

[0020] PAN-based carbon fiber and epoxy resin, the ratio is 40:60;

[0021] PAN-based carbon fiber and phenolic resin, the ratio is 35:65;

[0022] Asphalt-based carbon fiber and polyimide resin, the ratio is 40:60;

[0023] Asphalt-based carbon fiber and epoxy resin, the ratio is 50:50;

[0024] Asphalt-based carbon fiber and phenolic resin, the ratio is 45:55.

[0025] Preferably, the carbon fiber pretreatment step in S3 is:

[0026] S31. Use ethanol solvent to clean the carbon fiber surface to remove grease, dust and other contaminants to ensure good surface cleanliness;

[0027] S32, etching the carbon fiber with hydrochloric acid to increase its surface roughness, thereby improving the bonding strength with the matrix material;

[0028] S33, using plasma technology to treat the carbon fiber surface, introducing carboxyl functional groups, and improving the chemical compatibility with the resin;

[0029] S34, a coupling agent coated on the surface of the carbon fiber to enhance the interfacial adhesion between the carbon fiber and the resin;

[0030] S35. Through high temperature annealing, the structure of carbon fiber can be improved and its performance can be enhanced:

[0031] The resin modification improves the thermal stability and heat resistance of the resin, enhances the strength and rigidity of the composite material, and improves the wear resistance by adding a silane high-temperature stabilizer.

[0032] Preferably, the composite structure design of the filter material in S4 determines the combination and thickness of the inner and outer layer materials through the ratio of carbon fiber and resin obtained in S1, and designs the arrangement and direction of the fibers according to the load requirements and the expected use environment.

[0033] Preferably, in the composite material of S5, the resin is injected and pushed into the carbon fiber by pressure in a closed mold to ensure complete impregnation. After the impregnation is completed, the material is gently stirred with a scraper or brush to expel bubbles to ensure that there are no bubbles affecting the bonding effect.

[0034] Preferably, in S6, the composite material is placed inside a mold and heated for curing, and the heating temperature is 100-400°C.

[0035] Preferably, the high temperature resistant protective coating applied in S7 is a ceramic coating.

[0036] Preferably, an ultrahigh temperature resistant carbon fiber composite filter material is processed by the above-mentioned ultrahigh temperature resistant carbon fiber composite filter material production system.

[0037] The present invention provides an ultra-high temperature resistant carbon fiber composite filter material and a production system thereof. It has the following beneficial effects:

[0038] 1. Before actual production, the present invention verifies material properties by computer simulation of the resin and carbon fiber ratio, which significantly reduces the time and resource investment required for subsequent experiments. At the same time, it can also reduce the risks caused by material inapplicability, ensure the consistency and repeatability of the performance of each batch of composite materials, reduce performance fluctuations caused by differences in material proportions, select suitable resins and carbon fibers, and thus obtain high-temperature resistant and durable composite filter materials, effectively reducing the risks caused by material inapplicability, improving production efficiency, and reducing unnecessary waste.

[0039] 2. The present invention improves the surface properties of carbon fibers by modifying the resin and carbon fibers before compounding, thereby improving the mechanical properties and durability of the composite material.

[0040] 3. The present invention discharges air bubbles after impregnation to ensure that the resin or other impregnation liquid can penetrate into the gaps and surface of the fiber more evenly and deeply, thereby enhancing the adhesion between the fiber and the resin and improving the overall performance of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 It is a schematic diagram of the simulation results of the present invention. DETAILED DESCRIPTION

[0042] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] Embodiment:

[0044] The embodiment of the present invention provides a system for producing ultra-high temperature resistant carbon fiber composite filter material, comprising the following steps: S1, optimizing the dosage through computer simulation technology to predict the best material combination ratio;.

[0045] The specific steps of computer simulation ratio are as follows: S11. First, the physical and chemical property data of different types of fibers and resins are collected by computer, including strength, modulus, weight, temperature resistance, corrosion resistance, etc. These data can be derived from experimental tests and literature data. The selected carbon fibers include PAN-based carbon fibers and asphalt-based carbon fibers. The selected resins include polyimide, epoxy resin and phenolic resin.

[0046] S12. Use finite element analysis (FEA) software to establish a performance model of carbon fiber composite materials and simulate the performance changes of composite materials under different conditions;

[0047] S13. Apply the particle swarm optimization algorithm to iteratively analyze the model to find the optimal fiber-resin ratio, predict the material's strength, stiffness, weight ratio and other performance indicators under specific load conditions, and evaluate the composite material's strength, stiffness and fatigue life under different conditions through the simulated stress and strain distribution diagrams;

[0048] S14, experimentally verifying the optimal ratio scheme generated by computer simulation to ensure that the simulation results are consistent with the actual performance;

[0049] The experimental tests in S11 evaluate the physical and chemical properties of fibers and resins through tensile tests, compression tests, thermogravimetric analysis, differential scanning calorimetry, etc., and the obtained data are compiled into a computer database.

[0050] Embodiment 1:

[0051] S2 selected PAN-based carbon fiber and polyimide resin as the composite material with a ratio of 30:70.

[0052] S3 pre-treats PAN-based carbon fibers and modifies polyimide resin;

[0053] S31. Use ethanol solvent to clean the surface of PAN-based carbon fiber to remove grease, dust and other pollutants to ensure good surface cleanliness;

[0054] S32, etching the PAN-based carbon fiber with hydrochloric acid to increase its surface roughness, thereby improving the bonding strength with the matrix material;

[0055] S33, using plasma technology to treat the surface of PAN-based carbon fibers, introducing carboxyl functional groups, and improving the chemical compatibility with the resin;

[0056] S34, a coupling agent coated on the surface of PAN-based carbon fiber to enhance its interfacial adhesion with polyimide resin;

[0057] S35. High temperature annealing can improve the structure of PAN-based carbon fiber and enhance its performance: Polyimide resin modification can improve the thermal stability and heat resistance of polyimide resin by adding silane high temperature stabilizer, enhance the strength and stiffness of composite materials, and improve wear resistance.

[0058] S4. Composite structure design of composite filter material: The combination and thickness of inner and outer layer materials are determined by the ratio of PAN-based carbon fiber and polyimide resin obtained in S1, and the arrangement and direction of the fibers are designed according to the load requirements and the expected use environment.

[0059] S5. In a closed mold, inject the polyimide resin and push the polyimide resin into the PAN-based carbon fiber by pressure to ensure complete impregnation. After the impregnation is completed, gently stir the material with a scraper or brush to expel bubbles to ensure that there are no bubbles affecting the bonding effect. The PAN carbon fiber is combined with the polyimide resin matrix through the impregnation treatment to form a high-strength, lightweight composite material. The heating temperature is 330°C.

[0060] S6. Place the composite material inside the mold to solidify and cool.

[0061] S7. The surface of the formed composite filter material is polished and ground, and a ceramic coating and a high temperature resistant coating are applied.

[0062] S8. Obtain a formed carbon fiber composite filter material with a filtration efficiency exceeding 97.8% and an ultra-high temperature resistance of 300°C.

[0063] Example 2: S2 selects PAN-based carbon fiber and epoxy resin as the composite material with a ratio of 40:60.

[0064] S3 pre-treats PAN-based carbon fibers and modifies epoxy resin;

[0065] S31. Use ethanol solvent to clean the surface of PAN-based carbon fiber to remove grease, dust and other pollutants to ensure good surface cleanliness;

[0066] S32, etching the PAN-based carbon fiber with hydrochloric acid to increase its surface roughness, thereby improving the bonding strength with the matrix material;

[0067] S33, using plasma technology to treat the surface of PAN-based carbon fibers, introducing carboxyl functional groups, and improving the chemical compatibility with the resin;

[0068] S34, a coupling agent coated on the surface of PAN-based carbon fiber to enhance its interfacial adhesion with polyimide resin;

[0069] S35. Through high temperature annealing, the structure of PAN-based carbon fiber can be improved and its performance can be enhanced: modification of epoxy resin, adding butadiene-acrylate copolymer to epoxy resin, improving toughness through the formation of dispersed phase, and improving its mechanical properties, chemical resistance, thermal stability and ductility.

[0070] S4. Composite structure design of composite filter material: The combination and thickness of inner and outer layer materials are determined by the ratio of PAN-based carbon fiber and epoxy resin obtained in S1, and the arrangement and direction of the fibers are designed according to the load requirements and the expected use environment.

[0071] S5. In a closed mold, inject and push the epoxy resin into the PAN-based carbon fiber by pressure to ensure complete impregnation. After the impregnation is completed, gently stir the material with a scraper or brush to expel bubbles to ensure that there are no bubbles affecting the bonding effect. The PAN carbon fiber is combined with the epoxy resin matrix through the impregnation process to form a high-strength, lightweight composite material. The heating temperature is 150°C.

[0072] S6. Place the composite material inside the mold to solidify and cool.

[0073] S7. The surface of the formed composite filter material is polished and ground, and a ceramic coating and a high temperature resistant coating are applied.

[0074] S8. Obtain a formed carbon fiber composite filter material with a filtration efficiency exceeding 95.6% and an ultra-high temperature resistance of 120°C.

[0075] Example 3: S2 selects PAN-based carbon fiber and phenolic resin as the composite material with a ratio of 35:65.

[0076] S3 pre-treats PAN-based carbon fibers and modifies phenolic resin;

[0077] S31. Use ethanol solvent to clean the surface of PAN-based carbon fiber to remove grease, dust and other pollutants to ensure good surface cleanliness;

[0078] S32, etching the PAN-based carbon fiber with hydrochloric acid to increase its surface roughness, thereby improving the bonding strength with the matrix material;

[0079] S33, using plasma technology to treat the surface of PAN-based carbon fibers, introducing carboxyl functional groups, and improving the chemical compatibility with the resin;

[0080] S34, a coupling agent coated on the surface of PAN-based carbon fiber to enhance its interfacial adhesion with phenolic resin;

[0081] S35. Through high temperature annealing, the structure of PAN-based carbon fiber can be improved and its performance can be enhanced: modification of phenolic resin, adding melamine for cross-linking reaction, and enhancing the thermal stability and chemical resistance of phenolic resin.

[0082] S4. Composite structure design of composite filter material: The combination and thickness of inner and outer layer materials are determined by the ratio of PAN-based carbon fiber and phenolic resin obtained in S1, and the arrangement and direction of the fibers are designed according to the load requirements and the expected use environment.

[0083] S5. In a closed mold, inject phenolic resin and push it into the PAN-based carbon fiber by pressure to ensure complete impregnation. After the impregnation is completed, gently stir the material with a scraper or brush to expel bubbles to ensure that there are no bubbles affecting the bonding effect. The PAN carbon fiber is combined with the phenolic resin matrix through the impregnation process to form a high-strength, lightweight composite material. The heating temperature is 160°C.

[0084] S6. Place the composite material inside the mold to solidify and cool.

[0085] S7. The surface of the formed composite filter material is polished and ground, and a ceramic coating and a high temperature resistant coating are applied.

[0086] S8, obtaining a formed carbon fiber composite filter material with a filtration efficiency exceeding 92.3% and an ultra-high temperature resistance of 180°C;

[0087] Embodiment 4: S2 selects asphalt-based carbon fiber and phenolic resin as the composite material, with a ratio of 45:55.

[0088] S3 pre-treats the asphalt-based carbon fiber and modifies the phenolic resin;

[0089] S31, heating the asphalt to its softening point to dissolve it and form a viscous asphalt slurry, and spinning the asphalt solution into fibers through a spinning device, usually by wet spinning or dry spinning;

[0090] S32, pre-oxidizing the spun asphalt fibers, heating them to 250° C. in air to cause an oxidation reaction in the fibers to form a stable cross-linked structure, thus laying a foundation for subsequent carbonization;

[0091] S33, placing the pre-oxidized fiber in nitrogen and heating it at a high temperature of 2000°C to decompose the organic matter inside the fiber to form carbon material, while the generated gas is discharged to reduce impurities;

[0092] S34, using pickling treatment to improve the surface properties of carbon fiber, enhance the adhesion of the fiber and the compatibility with the matrix;

[0093] S35. Performing subsequent processes such as curing and heat treatment on the prepared composite material:

[0094] Modification of phenolic resin by adding melamine for cross-linking reaction to enhance the thermal stability and chemical resistance of phenolic resin.

[0095] S4. Composite structure design of composite filter material: The combination and thickness of the inner and outer layer materials are determined by the ratio of asphalt-based carbon fiber and phenolic resin obtained in S1, and the arrangement and direction of the fibers are designed according to the load requirements and the expected use environment.

[0096] S5. In a closed mold, inject phenolic resin and push it into the asphalt-based carbon fiber by pressure to ensure complete impregnation. After the impregnation is completed, gently stir the material with a scraper or brush to expel bubbles to ensure that there are no bubbles affecting the bonding effect. The asphalt carbon fiber is combined with the phenolic resin matrix through the impregnation treatment to form a high-strength, lightweight composite material. The heating temperature is 160°C.

[0097] S6. Place the composite material inside the mold to solidify and cool.

[0098] S7. The surface of the formed composite filter material is polished and ground, and a ceramic coating and a high temperature resistant coating are applied.

[0099] S8, obtaining a formed carbon fiber composite filter material with a filtration efficiency exceeding 88.5% and a super-high temperature resistance of 160° C. Embodiment 5: S2, selecting asphalt-based carbon fiber and polyimide resin as composite materials, with a ratio of 60:40.

[0100] S3 pre-treats the asphalt-based carbon fiber and modifies the polyimide resin;

[0101] S31, heating the asphalt to its softening point to dissolve it and form a viscous asphalt slurry, and spinning the asphalt solution into fibers through a spinning device, usually by wet spinning or dry spinning;

[0102] S32, pre-oxidizing the spun asphalt fibers, heating them to 250° C. in air to cause an oxidation reaction in the fibers to form a stable cross-linked structure, thus laying a foundation for subsequent carbonization;

[0103] S33, placing the pre-oxidized fiber in nitrogen and heating it at a high temperature of 2000°C to decompose the organic matter inside the fiber to form carbon material, while the generated gas is discharged to reduce impurities;

[0104] S34, using pickling treatment to improve the surface properties of carbon fiber, enhance the adhesion of the fiber and the compatibility with the matrix;

[0105] S35. Performing subsequent processes such as curing and heat treatment on the prepared composite material:

[0106] Polyimide resin modification improves the thermal stability and heat resistance of polyimide resin, enhances the strength and stiffness of composite materials, and improves wear resistance by adding silane high temperature stabilizer.

[0107] S4. Composite structure design of composite filter material: The combination and thickness of inner and outer layer materials are determined by the ratio of asphalt-based carbon fiber and polyimide resin obtained in S1, and the arrangement and direction of the fibers are designed according to the load requirements and the expected use environment.

[0108] S5. In a closed mold, inject the polyimide resin and push the polyimide resin into the asphalt-based carbon fiber by pressure to ensure complete impregnation. After the impregnation is completed, gently stir the material with a scraper or brush to expel bubbles to ensure that there are no bubbles affecting the bonding effect. The asphalt carbon fiber is combined with the polyimide resin matrix through the impregnation treatment to form a high-strength, lightweight composite material. The heating temperature is 340°C.

[0109] S6. Place the composite material inside the mold to solidify and cool.

[0110] S7. The surface of the formed composite filter material is polished and ground, and a ceramic coating and a high temperature resistant coating are applied.

[0111] S8. A formed carbon fiber composite filter material with a filtration efficiency exceeding 85.5% and an ultra-high temperature resistance of 260° C. is obtained.

[0112] Example 6: S2 selects asphalt-based carbon fiber and epoxy resin as the composite material with a ratio of 50:50.

[0113] S3 pre-treats the asphalt-based carbon fiber and modifies the epoxy resin;

[0114] S31, heating the asphalt to its softening point to dissolve it and form a viscous asphalt slurry, and spinning the asphalt solution into fibers through a spinning device, usually by wet spinning or dry spinning;

[0115] S32, pre-oxidizing the spun asphalt fibers, heating them to 250° C. in air to cause an oxidation reaction in the fibers to form a stable cross-linked structure, thus laying a foundation for subsequent carbonization;

[0116] S33, placing the pre-oxidized fiber in nitrogen and heating it at a high temperature of 2000°C to decompose the organic matter inside the fiber to form carbon material, while the generated gas is discharged to reduce impurities;

[0117] S34, using pickling treatment to improve the surface properties of carbon fiber, enhance the adhesion of the fiber and the compatibility with the matrix;

[0118] S35. Performing subsequent processes such as curing and heat treatment on the prepared composite material:

[0119] Modification of epoxy resin, adding butadiene-acrylate copolymer to epoxy resin, improving toughness through the formation of dispersed phase, and improving its mechanical properties, chemical resistance, thermal stability and ductility.

[0120] S4. Composite structure design of composite filter material: The combination and thickness of inner and outer layer materials are determined by the ratio of asphalt-based carbon fiber and epoxy resin obtained in S1, and the arrangement and direction of the fibers are designed according to the load requirements and the expected use environment.

[0121] S5. In a closed mold, inject epoxy resin and push the epoxy resin into the asphalt-based carbon fiber by pressure to ensure complete impregnation. After the impregnation is completed, gently stir the material with a scraper or brush to expel bubbles to ensure that there are no bubbles affecting the bonding effect. The asphalt carbon fiber is combined with the epoxy resin matrix through the impregnation process to form a high-strength, lightweight composite material. The heating temperature is 130°C.

[0122] S6. Place the composite material inside the mold to solidify and cool.

[0123] S7. The surface of the formed composite filter material is polished and ground, and a ceramic coating and a high temperature resistant coating are applied.

[0124] S8. Obtain a formed carbon fiber composite filter material with a filtration efficiency exceeding 90.2% and an ultra-high temperature resistance of 100°C.

[0125] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A system for producing ultra-high temperature resistant carbon fiber composite filter material, characterized in that: The method comprises the following steps: S1, optimizing the dosage by computer simulation technology to predict the best material combination ratio; S2, selecting high-quality carbon fiber and resin as composite resin materials according to the simulation results; S3, pre-treating the carbon fiber and modifying the resin; S4. Design of filter material composite structure; S5, combining carbon fibers with a polyimide resin matrix through an impregnation process to form a high-strength, lightweight composite material; S6, placing the composite material inside the mold for solidification and cooling; S7, polishing and grinding the surface of the formed composite filter material, and applying a high temperature resistant coating; S8, obtaining a formed ultra-high temperature resistant carbon fiber composite filter material.

2. The ultra-high temperature resistant carbon fiber composite filter material production system according to claim 1, characterized in that: The specific steps of the computer simulation ratio are as follows: S11, first, the physical and chemical property data of different types of fibers and resins are collected by computer, including strength, modulus, weight, temperature resistance, corrosion resistance, etc., which can be derived from experimental tests and literature data. The selected carbon fibers include PAN-based carbon fibers and asphalt-based carbon fibers, and the selected resins include polyimide, epoxy resin and phenolic resin; S12. Use finite element analysis (FEA) software to establish a performance model of carbon fiber composite materials and simulate the performance changes of composite materials under different conditions; S13. Apply the particle swarm optimization algorithm to iteratively analyze the model to find the optimal fiber-resin ratio, predict the material's strength, stiffness, weight ratio and other performance indicators under specific load conditions, and evaluate the composite material's strength, stiffness and fatigue life under different conditions through the simulated stress and strain distribution diagrams; S14. Experimentally verify the optimal ratio scheme generated by computer simulation to ensure that the simulation results are consistent with the actual performance.

3. The ultra-high temperature resistant carbon fiber composite filter material production system according to claim 2, characterized in that: The experimental tests in S11 evaluate the physical and chemical properties of the fiber and the resin by means of tensile testing, compression testing, thermogravimetric analysis, differential scanning calorimetry, etc., and the obtained data are collected in a computer database.

4. The ultra-high temperature resistant carbon fiber composite filter material production system according to claim 2, characterized in that: The computer simulation ratio results are as follows: PAN-based carbon fiber and polyimide resin, the ratio is 30:70; PAN-based carbon fiber and epoxy resin, the ratio is 40:60; PAN-based carbon fiber and phenolic resin, the ratio is 35:65; Asphalt-based carbon fiber and polyimide resin, the ratio is 40:60; Asphalt-based carbon fiber and epoxy resin, the ratio is 50:50; Asphalt-based carbon fiber and phenolic resin, the ratio is 45:

55.

5. The ultra-high temperature resistant carbon fiber composite filter material production system according to claim 1, characterized in that: The carbon fiber pretreatment step in S3 is: S31. Use ethanol solvent to clean the carbon fiber surface to remove grease, dust and other contaminants to ensure good surface cleanliness; S32, etching the carbon fiber with hydrochloric acid to increase its surface roughness, thereby improving the bonding strength with the matrix material; S33, using plasma technology to treat the carbon fiber surface, introducing carboxyl functional groups, and improving the chemical compatibility with the resin; S34, a coupling agent coated on the surface of the carbon fiber to enhance the interfacial adhesion between the carbon fiber and the resin; S35. Through high temperature annealing, the structure of carbon fiber can be improved and its performance can be enhanced: The resin modification improves the thermal stability and heat resistance of the resin, enhances the strength and rigidity of the composite material, and improves the wear resistance by adding a silane high-temperature stabilizer.

6. The ultra-high temperature resistant carbon fiber composite filter material production system according to claim 1, characterized in that: The composite structure design of the filter material in S4 determines the combination and thickness of the inner and outer layer materials through the ratio of carbon fiber and resin obtained in S1, and designs the arrangement and direction of the fibers according to the load requirements and the expected use environment.

7. The ultra-high temperature resistant carbon fiber composite filter material production system according to claim 1, characterized in that: The composite material in the S5 is in a closed mold, and the resin is injected and pushed into the carbon fiber by pressure to ensure complete impregnation. After the impregnation is completed, the material is gently stirred with a scraper or brush to expel bubbles to ensure that there are no bubbles that affect the bonding effect.

8. The ultra-high temperature resistant carbon fiber composite filter material production system according to claim 1, characterized in that: In S6, the composite material is placed inside the mold and heated for curing, and the heating temperature is 100-400°C.

9. The ultra-high temperature resistant carbon fiber composite filter material production system according to claim 1, characterized in that: The high temperature resistant protective coating applied in S7 is a ceramic coating.

10. An ultra-high temperature resistant carbon fiber composite filter material, characterized in that: The ultra-high temperature resistant carbon fiber composite filter material is processed by the production system of claims 1-9.